CO oxidation over the polyoxometalate-supported single-atom catalysts M1/POM (Fe, Co, Mn, Ru, Rh, Os, Ir, and Pt; POM = [PW12O40]3–): a computational study on the activation of surface oxygen species - Chun-Guang Liu; Li-Long, Zhang; Chen, Xue-Mei (Dalton transactions : an international journal of inorganic chemistry, 2019)
The discrete anionic structure of polyoxometalates (POMs) at the interface is more like a separate small “island”, which effectively prevents the diffusion of single atoms and prohibits the agglomeration and generation of metal particles; thus, POMs can enhance the sintering-resistant behavior and increase metal loading on the surface of single-atom catalysts (SACs). To explore the catalytic performance of POM-supported SACs for CO oxidation, we employed density functional theory (DFT) calculations to gain an understanding of some important aspects, including the CO adsorption, the formation of oxygen vacancies, and the activity of the surface oxygen species, of the catalytic system. Compared to previous theoretical studies, in which the catalytic behavior of POMs has been investigated based on the anionic unit with the highest negative charge, herein, we have constructed a model of the POM-supported SACs, which are neutral species. Our DFT calculations indicated that in the series of the SACs studied herein, (1) upon anchoring of a single metal atom on the POM surface, four key surface oxygen atoms were lifted from the POM surface to form a new interface, and thus, the surface oxygen species were activated; (2) CO adsorbed more strongly on the Ir, Os, Rh, Pt, and Ru sites than on the Fe, Mn, and Co sites; (3) it was easy to form an oxygen vacancy on the POM surface in the case of the Pt system when compared with the other systems; (4) the difference in the surface oxygen species for CO oxidation was remarkable, and the Oc atom at the catalyst interface had higher reactivity for CO oxidation as compared to the Ob atom in the Pt system studied herein; and (5) the single Pt atom served as an electron reservoir in the CO oxidation along the reaction pathway.